Interaksionisme Simbolik: Peran Kepemimpinan Dalam Pengambilan Keputusan - Diningrum Citraningsih; Hanifah Noviandari (Social Science Studies, 2022)
This article aims to determine the role of leadership in decision making where the role of a leader is an individual who has the ability to interact symbolically in society. This article attempts to explain the formulation of symbolic interactionism in leadership roles in decision making based on data sources from journals, books and other scientific articles. The implications of symbolic interactionism theory attached to the role of leadership in decision making are role theory and situation definition theory. Leaders act as individuals in the community who have the authority to make decisions to achieve organizational goals.